2023
DOI: 10.1002/smll.202207125
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐Containing Liposomes Decorated With Au Nanoparticles as Minimal Tunable Fusion Machinery

Abstract: Membrane fusion is essential for the basal functionality of eukaryotic cells. In physiological conditions, fusion events are regulated by a wide range of specialized proteins, operating with finely tuned local lipid composition and ionic environment. Fusogenic proteins, assisted by membrane cholesterol and calcium ions, provide the mechanical energy necessary to achieve vesicle fusion in neuromediator release. Similar cooperative effects must be explored when considering synthetic approaches for controlled mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Indeed, a recent study by Tahir et al demonstrated that MUS:OT NPs induce fusion between pure phosphatidylcholines (PC) liposomes, 17 and our group showed that the liposome cholesterol content can nely tune MUS:OT NP-induced fusion events. 18 Molecular Dynamics (MD) simulations, thanks to their high spatiotemporal resolution, have been successfully employed to shed light on the molecular mechanisms involved in the different stages of the fusion process, either spontaneous [19][20][21][22] or mediated by fusion agents. 17,[23][24][25] The presence of high free energy barriers makes the use of atomistic models challenging and calls for coarse-grained models and/or enhanced sampling techniques.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, a recent study by Tahir et al demonstrated that MUS:OT NPs induce fusion between pure phosphatidylcholines (PC) liposomes, 17 and our group showed that the liposome cholesterol content can nely tune MUS:OT NP-induced fusion events. 18 Molecular Dynamics (MD) simulations, thanks to their high spatiotemporal resolution, have been successfully employed to shed light on the molecular mechanisms involved in the different stages of the fusion process, either spontaneous [19][20][21][22] or mediated by fusion agents. 17,[23][24][25] The presence of high free energy barriers makes the use of atomistic models challenging and calls for coarse-grained models and/or enhanced sampling techniques.…”
mentioning
confidence: 99%
“…9 Here we build on the original denition of the x ch chain coordinate, modifying it to account for the presence of the fusogenic agent, a MUS:OT Au NP embedded in one of the two lipid bilayers. Our previous MD simulations based on a coarsegrained force eld revealed that the stalk rim constantly forms over a single Au NP, 18 consequently to the formation of a hydrophobic contact between a lipid tail of the top bilayer and transient hydrophobic defects on the NP, water-facing surface. This mechanism is consistent with the one described in the literature for NP-free membranes, with the only difference being that the contact is a lipid-NP one and not a lipid-lipid one.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] Most of these studies use functionalized gold nanoparticles. Though these nanoparticles can induce stalk formation, they are not capable to promote pore opening by themselves, and they use external factors such as addition of calcium 9,10 or heating of the nanoparticle 12 to continue the fusion process. Silica nanoparticles have also been used for membrane fusion, and while they can facilitate stalk and hemifusion diaphragm formation, they do not catalyze the formation of a fusion pore.…”
Section: Discussionmentioning
confidence: 99%